Vaccination coverage rate in the Braga Health Centre in birth cohorts from 1990 to 2005 (Portuguese Journal of Family Medicine and General Practice, 2007)
Aim: To determinate vaccine coverage of all vaccine included in Portuguese National Vaccination Program (PNVP), in 1990 to 2005 birth cohorts, in Braga Health Centre (BHC) and in their Health Extensions (HE). Type of Study: Observational cross-sectional study. Local: Braga Health Centre. Population: Individuals registered in each HE and HU of BHC, which belong to 1990 - 2005 birth cohorts. Methods: Sinus informatic program was used as information data source. Results: The attenuated polio vaccine and hepatitis B vaccine reached coverage levels higher to 95% in 2002, the Bacille Calmette-Guérin and measles, mumps and rubella vaccine in 2004 and the diphtheria-tetanus-pertussis vaccine (DTP) and Haemophilus influenzae b vaccine (Hib) in 2005. Vaccine coverage of combined vaccine against tetanus and diphtheria, of individual immunity, was always lower to 100% (values between 84 to 94%). Some HE maintains coverage levels very lower to internationally recommend. It was also verified that vaccines to which PNVP recommends more doses, such as DTP and Hib, have inferior coverage levels. Conclusions: It was demonstrated a progressive tendency to the improved coverage levels over time in BHC. However, values higher to 95% were only recently reached. Thus, the PNVP aims start to be acceptable achieve in younger birth cohorts. In this study were also described significant asymmetries in vaccine coverage levels that can delay the achievement of group immunity, being an important problem of public health..
Keywords: Portuguese National Vaccination Program; Vaccine Coverage; Braga Health Centre